Palliative care: forms of performing, principles of co-operation with family doctor - Pyszkowska, Jadwiga (Przewodnik Lekarza/Guide for GPs, 2007)
A palliative and hospice care programme is the answer to the needs of the patient and his relatives who are taking care of him during the illness and dying. The palliative care is performed by a multidisciplinary, skilled and qualified team of specialists. The terminal illness period is a time when the patient’s chronic disease is far advanced and you cannot use curative treatment procedures. The patient has the right to symptomatic treatment, to being cared and surrounded by relatives, has the right to being part of the family, at home. A good quality of life status of the patient is achieved by multidimensional procedures of specialist palliative care units by managing the pain and other symptoms (symptomatic treatment), alleviating psychic, spiritual and social suffering, and helping the family during the illness and after the patient’s death in the time of bereavement. These units support the family doctor, who, as the first doctor, should symptomatically treat the terminally ill patient.